AKUNTANSI DAN KAPITALISME - Adam, Helmy (Fakultas Ekonomi, UIN Maliki Malang, 2008)
Accountancy can form and be formed by environment where about the accountancy developed. Accountancy expanding in this time is notching from capitalism ideology. Capitalism born from rational values, liberalism values, and materialism values with understanding assuming society prosperity will only be obtainable production is well delivered to every individual giving infinite facility for resources management in reaching target. This artcleÂ aim at, providing conventional description accountancy ideology influencing theoretical concept forming accountancy.